Sauna bathing and their properties – empirical research and awareness of people based on anonymous surveys - Wcisło, Wojciech; Grużewska-Piotrowska, Kinga; Pająk, Monika; Hubka, Joanna; Grużewska, Agnieszka (Journal of Education, Health and Sport, 2023)
Introduction: Bathing at high temperatures has been a practice used for thousands of years in many cultures. High or low temperatures are considered a stress factor for the human body and are often a challenge to maintain homeostasis. Heat stress can be beneficial to human health, independent of other lifestyle factors. The aim of the study: The aim of the study was to assess the level of knowledge among people about sauna bathing, the benefits of its use and diseases that are contraindications to such bathing, as well as empirical research on sauna bathing habits based on anonymous surveys. Materials and methods: The research material was collected using an anonymous survey in May 2023. The obtained results were analyzed and verified on the basis of scientific literature and statistically processed using Microsoft Office Excel. Results: 87.5% of the respondents use the sauna, the majority - several times a year, and 15% - several times a week. For 77.1% of respondents using the sauna, it is a form of entertainment, but 15.2% treat it as a form of health prevention. Many respondents wrongly indicate contraindications to bathing in the sauna, and 73.3% of people do not know any effects of the sauna. Discussion and conclusions: Many respondents use the sauna, but most of them use it as a form of entertainment. Few people know the full effect of the sauna on the body and its multidirectionality. More than half of the respondents cannot name the contraindications to bathing in the sauna. As far as possible, the doctor should indicate people with, among others, increased cardiovascular risk, this form of prophylaxis.